2021
DOI: 10.1007/s10570-021-04210-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the influence of dispersion interactions on the elastic properties of crystalline cellulose

Abstract: Dispersion and electrostatic interactions both contribute significantly to the tight assembly of macromolecular chains within crystalline polysaccharides. Using dispersion-corrected density functional theory (DFT) calculation, we estimated the elastic tensor of the four crystalline cellulose allomorphs whose crystal structures that are hitherto available, namely, cellulose Ia, Ib, II, III I . Comparison between calculations with and without dispersion correction allows quantification of the exact contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Therefore the “effective” HB density that contributes to C22 is less than one per residue. The Young’s modulus decreased monotonously as the density of the interchain HBs decreased (Figure ) and was calculated to be 99.2, 52.8, and 30.6 GPa, respectively . With the dispersion switched off, these values decreased to 68.2, 26.2, and 12.6 GPa, thus being reduced by 31.0, 26.6, and 18.0 GPa, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore the “effective” HB density that contributes to C22 is less than one per residue. The Young’s modulus decreased monotonously as the density of the interchain HBs decreased (Figure ) and was calculated to be 99.2, 52.8, and 30.6 GPa, respectively . With the dispersion switched off, these values decreased to 68.2, 26.2, and 12.6 GPa, thus being reduced by 31.0, 26.6, and 18.0 GPa, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…In our recent study, we analyzed the effect of dispersion interactions on cellulose crystals, by switching the dispersion correction , on and off. Here, we apply the same approach to chitin and chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…In the transverse directions on the other hand, the situation is different, since covalent interactions can be expected to contribute less. DFT calculations (Chen et al 2021) show that dispersion interactions contribute around 50% of the stiffness in the direction perpendicular to the H-bonded planes, and about 30% in the direction parallel to the H-bonded planes (Fig. 2).…”
Section: Intermolecular H-bonds and The Formation Of Fibrilsmentioning
confidence: 99%
“…Quantum models have related the details of cellulose crystalline structure to results from vibrational and NMR spectroscopy and were used to estimate the energetics of different cross-sectional shapes of CMFs, for example, ( Kubicki et al, 2018 ; Yang et al, 2018 ; Yang and Kubicki, 2020 ). In another vein, recent quantum modeling efforts concluded that dispersion forces (attractions due to induced dipoles) contributed substantially to the mechanical properties of cellulose, in some directions even more than did hydrogen bonding ( Chen et al, 2021 ). This insight runs counter to the common notion that cellulose stiffness, insolubility, and other properties are primarily due to dense hydrogen bonding within the microfibril ( Wohlert et al, 2021 ).…”
Section: Cell Wall Models: Relating Structure To Mechanics and Polyme...mentioning
confidence: 99%